If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 2(x + 1) + 3(x + 2) = 8 Reorder the terms: 3x + 2(1 + x) + 3(x + 2) = 8 3x + (1 * 2 + x * 2) + 3(x + 2) = 8 3x + (2 + 2x) + 3(x + 2) = 8 Reorder the terms: 3x + 2 + 2x + 3(2 + x) = 8 3x + 2 + 2x + (2 * 3 + x * 3) = 8 3x + 2 + 2x + (6 + 3x) = 8 Reorder the terms: 2 + 6 + 3x + 2x + 3x = 8 Combine like terms: 2 + 6 = 8 8 + 3x + 2x + 3x = 8 Combine like terms: 3x + 2x = 5x 8 + 5x + 3x = 8 Combine like terms: 5x + 3x = 8x 8 + 8x = 8 Add '-8' to each side of the equation. 8 + -8 + 8x = 8 + -8 Combine like terms: 8 + -8 = 0 0 + 8x = 8 + -8 8x = 8 + -8 Combine like terms: 8 + -8 = 0 8x = 0 Solving 8x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Divide each side by '8'. x = 0 Simplifying x = 0
| 5(3a+1)=2(2a-1) | | 9x+9=7x+25 | | 5+6+7=303585 | | 2x+3x=13 | | 9+4+7=366329 | | 3(y+2)=2(y-1) | | 23-4x=11 | | 3(2x-7)=8x-5 | | .6+(.6-.5)*.85= | | 3pq-6p^2= | | .6+(.5-.6)*.85= | | 6(x-7)=4x-8 | | 5(t-3)+7t=6(2t+3)-11 | | 8x-6=7x-6 | | 4x-20=3x+9 | | |2x-3|=15 | | y=-10x+52 | | 3a+10=a^2 | | 4g=52 | | 3x+8=9x-46 | | 3s=81 | | x+x+1+x+2=66 | | 12w-19w=56 | | 125x-5x^3=0 | | 125-5x^3=0 | | (m-3)(m+3)-(m+7)(m+7)= | | 8(x+8)-21= | | 11(5a)= | | 2x-5x+7x-8x= | | 8(t-2)=3(t-9) | | 3k=(-0.857142) | | -13r+10=5r-46 |